Flint corn silage management: influence of maturity stage, inoculation with Lentilactobacillus buchneri, and storage time on fermentation pattern, aerobic stability, and nutritional characteristics - Rossi, Luis G.; Andrade, Marina E. B.; Rabelo, Carlos H. S.; Siqueira, Gustavo R.; Vicente, Eduardo F.; Silva, Wilton L.; Silva, Matheus M.; Reis, Ricardo A. (Frontiers in Microbiology, 2023)
High quality corn silage depends on factors such as corn type, stage of crop development at harvest time, fermentation time, in addition to use or not of inoculants. This study aimed to investigate the impact of maturity stage, bacterial inoculation, and storage time on fermentation, aerobic stability, and nutritional characteristics of flint corn silage and their implications for corn silage management. A flint corn hybrid was harvested very early, early and medium (at 250, 300 and 350 g dry matter (DM)/kg as fed, respectively) and ensiled in mini-silos without (control) or with Lentilactobacillus buchneri CNCM I-4323 at 1 × 105 cfu/g for 120, 240 and 360 d to investigate how these factors interact with each other. There was only a small increase (7 g/kg; P = 0.003) in starch digestibility (starch-D) in the silages stored for 360 d when compared to that stored for 240 d, but with no difference for 120 d. Despite the reduced starch-D (526 vs. 694 g/kg starch; P < 0.001), silages produced from medium harvest had higher (P < 0.001) starch content (317 vs. 137 g/kg DM) and higher amount of digestible starch (169 vs. 98.5 g/kg DM; P < 0.001) compared to very early harvest. The 2-way interactions (inoculation × storage time and maturity × storage time) showed that inoculation of corn silage with L. buchneri increased (P < 0.001) the aerobic stability, and that more mature crop silage had higher aerobic stability (140 h; P = 0.036) than the others (118 and 48.5 h for those silages from very early and early harvest). The storage for a longer time (>120 d) with the goal of increasing silage digestibility did not occur. Harvesting whole-crop flint corn with 300 to 350 g/kg DM is desirable to have higher DM yield and starch accumulation. Inoculation with L. buchneri is recommended to preserve the silage against aerobic deterioration. This study has shown the importance of harvesting flint corn at the right time, and the need for inoculation with L. buchneri to ensure greater yield, starch accumulation, and silage preservation, if 120 days of storage are not exceeded.